Negotiating Climate Change in Crisis (Open Book Publishers, 2021)
"Climate change negotiations have failed the world. Despite more than thirty years of high-level, global talks on climate change, we are still seeing carbon emissions rise dramatically. This edited volume, comprising leading and emerging scholars and climate activists from around the world, takes a critical look at what has gone wrong and what is to be done to create more decisive action.